Diet in pregnant women in preventing stunting: a scoping review - Mamat Lukman; Femmy Aditya Purnama Sejati; Sandra Pebrianti; Iwan Shalahuddin (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Stunting is a chronic nutritional health problem in toddlers. However, stunting can be prevented, one of which is by maintaining maternal health during pregnancy, namely diet and nutritional intake. Therefore, pregnant women are expected to be able to control their diet. This study aims to provide an overview of diet in pregnant women as a prevention of stunting events. This study used the scoping review method. The databases used are EBSCOhost and PubMed with a search for relevant studies published from 2017-2022. The inclusion criteria for selected articles are English-language articles, fulltext articles. Excluded articles are articles that use meta-analysis and systematic review methods. The results obtained were 8 articles, of which seven articles showed the type and healthy diet of the significance of increasing birth weight which is an indicator of growth and incidence of stunting. In detail, the type and healthy diet in pregnant women is to increase food intake by 15% than usual with the consumption of the main food 3x a day plus 2x interludes/snacks consisting of more than 5 types of food (MDD-W) with more than 4 servings/week in each type, so that the nutrition of pregnant women remains fulfilled, accompanied by multivitamin supplementation (vitamin B-1 (thiamin), B-2 (riboflavin),  B-6, niacin, B-12, C, and E), calcium, folic acid and IFA tablets. The conclusion obtained is that the type and healthy diet in pregnant women produces a significant good effect on birth weight in preventing stunting. As well as demographic factors affecting the diet in pregnant women.